Pengaruh Pendekatan Contextual Teaching Learning Pada Topik Peluang Terhadap Motivasi dan Hasil Belajar - Fatih Al Farisy, Nuril Hafidz; Sari, Anisa Fatwa (Mathematics Department, 2017)
This research is motivated by mathematics learning which the concept is always given by the teacher without any explanation about the usefulness of mathematics material of chance occurrence in everyday life so that students do not know the benefit of learning chance of the occurrence so that students less active in learning chance of occurrence and result in lack of motivation learn student so result Student learning is low. One of the efforts taken by researchers is to apply the learning model Contextual Teaching Learning. The purpose of this research is to know the influence of learning model Contextual Teaching Learning to motivation and student learning outcomes. Contextual Teaching Learning is expected to increase students' motivation and with increasing motivation of students is expected to improve their learning outcomes on learning mathematics material opportunities occurrence. This study aims to determine the Effect of Contextual Teaching Learning Approach to Student Motivation Viewed From Student Learning Outcomes On Material Event Opportunity. This research method using r test between motivation and mathematics learning result with population in this research is class 11 in one of school in Surabaya. This research proves that the researcher's initial hypothesis is correct. Based on the results of this study it can be concluded that the Contextual Teaching Learning Approach will increase students' motivation in terms of student learning outcomes.